Sixteenth Annual Conference of The Association of Muslim Social Scientists (American Journal of Islam and Society, 1987)
The Association of Muslim Social Scientists (AMSS) held its SixteenthAnnual Conference at the ISNA headquarters in Plainfield, Indiana, October9-11, 1987. Registration listed about 200 participants from the United States,Canada, the United Kingdom, Pakistan, Trinidad, and other countries. Theinaugural session on October 9 provided a hospitable setting for camaraderie.Eloquent and spirited speeches by Iqbal Unus, Conference Chairman; lbrahimSyed, AMSE Program Chairman; and Mushtaqur Rahman, AMSS ProgramChairman, set the stage for the conference and the sessions.Chaired by Salahuddin Malik, AMSS Vice-president, the first session onPolitical Science was held on Friday evening after Salat-ul Maghrib. HashemAl-Jaseem of the University of California was the first to present his paperon Islam and Politics. He was followed by Taysir Nashif of Essex CountyCollege, who pleaded for a Nuclear Free Zone in the Middle East. LouaySafi of Wayne State University concluded the session with his presentationof War and Peace in Islam.This session was so lively and discussions so absorbing that no time wasleft for the following session scheduled for the same evening. Conferees preferredto postpone the second session rather than to conclude the discussions.It was heartening that every conferee maintained the Islamic tradition of conductingdebates in a spirit of good humor, disagreeing without beingdisagreeable.The first full day of the conference, Saturday, October 10, began with aTilawat-e-Quran, and a session on Education. Chaired by M.A.W. Fakhri ofChicago State University, the session had two presentations. Hakim Rashidof Howard University opened the session with his paper on “SocializatiodEducationof Muslim Children in America”. He was followed by NimatHafez Barzangi of Cornell University, who presented her paper on “Perceptionsof the Islamic Belief System: The Muslims in North America. Followingthe session on education, two concurrent sessions were held on Sociologyand History dealing with Muslim minorities. This was the first time the strategyof concurrent sessions was ever tried in the AMSS. The sociology sessionChairperson, Ilyas Baynus of the State University of New York, first invited ...